Carbonate melt-based flue gas desulphurisation: material balance and economic advantage. (2018) - Kaplan, Valery; Wachtel, Ellen; Dosmukhamedov, Nurlan; Lubomirsky, Igor
We have recently proposed a two-stage process for scrubbing sulphur from flue gas of coal-fired power plants: 1) the gas is brought into contact with a (Na, K, Li)-carbonate eutectic melt, producing sulphates; 2) the eutectic is regenerated by purging with CO from coal combustion, and recycled. Only the coal requires continual replenishing. In the current work, a combined scrubbing/regeneration flow diagram is presented and the material balance calculated. The economic advantages of the dual process are evaluated, taking into consideration high value end-products and the effect of sulphur content on the quantity of additional coal required for CO production. [Received: March 24, 2017; Accepted: July 17, 2017]